Economic evaluation of cholinesterase inhibitor therapy for dementia: comparison of Alzheimer's disease and Dementia with Lewy bodies. - Gustavsson, A; Van Der Putt, R; Jönsson, L; Mcshane, R (2009)
OBJECTIVE: To assess the cost effectiveness of cholinesterase inhibitor (ChEI) treatment in patients with Alzheimer's disease (AD) and Dementia with Lewy bodies (DLB). METHOD: We used 4-month open label follow-up data from routine memory clinic patients. There were 852 patients with AD and 112 with DLB. We applied three predictive models to estimate clinical and economic outcomes at five years, comparing AD and DLB patients with hypothetical untreated controls. RESULTS: The mean improvement in MMSE in 852 AD patients was 0.57 (SD 3.4) at 4 months, and in the subgroup with baseline MMSE of 10-20 (moderate) was 1.6 (SD 3.7). Overall, the 112 DLB patients improved by 1.4 (SD 3.7). DLB patients with an MMSE 10-20 improved by 3.1 (SD 4.5) points. These efficacy data were input into the SHTAC, microsimulation and Markov models and produced estimated costs per QALY gained (CQG) for all AD of pound194,066, pound67,904 and pound123,935 respectively. In comparison, the CQGs for all DLB were pound46,794, pound2,706 and pound35,922. For the moderate subgroups only the SHTAC and microsimulation models were applicable. These gave CQG estimates for moderate AD of pound39,664 and cost saving respectively. For moderate DLB, both estimates were cost saving. CONCLUSION: The cost per QALY gained of cholinesterase treatment of all patients with DLB (including those with MMSE outside the 10-20 range) is comparable to that of patients with moderate AD, and is probably cost saving.